KORBAN KEKERASAN SEKSUAL DI KAMPUS: PENGALAMAN NARATIF - Atika, Atika (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2023)
This study examines the dynamics of sexual violence in the campus environment, focusing on student perceptions and attitudes, institutional responses, and the social implications that arise. The findings show that social norms that support aggressive masculine behavior, ineffective campus policies, and lack of education about sexual violence are the main factors influencing the prevalence of sexual violence. Many victims feel that their reports are not taken seriously and do not receive adequate support, both from friends and institutions. Victim-blaming attitudes are still common, which hampers reporting and case handling efforts. This research emphasizes the importance of campus policy reform, improved educational programs, and better support for victims to create a safe and inclusive environment. Implications of these findings include the need for a thorough evaluation of existing policies and procedures, as well as the development of programs aimed at increasing awareness and understanding of sexual violence among students